GIUSEPPE VERDI: UN BALLO IN MASCHERA - Júlia KÖPECZI KIRKÓSA (Studia Universitatis Babeş-Bolyai. Musica)
The following study will attempt to depict the creation process of one of Verdi’s most dramatic operas – Un Ballo in Maschera. As it was the case many times throughout history, the genesis of this work was also influenced by the politics of the day. Due to strenuous political times, Verdi was compelled to change the setting of his opera and also alter the names of the characters in order not to create havoc for the entire art scene on Italy. Although one might state that the composer was obliged to make compromises, one could safely say that these did not affect by any means the message of the opera or the dramatic impact it had then, on the day of the premiere or even so today, 151 years after its creation.